Isolation of a feline-derived feline panleukopenia virus with an A300P substitution in the VP2 protein and confirmation of its pathogenicity in dogs - Jiakang Li; Jiajia Peng; Yue Zeng; Ying Wang; Luying Li; Yiran Cao; Longlong Cao; QingXiu Chen; Zijun Ye; Dengyuan Zhou; Shengbo Cao; Qiuyan Li (BMC, 2024)
Abstract Feline panleukopenia virus (FPV) is a single-stranded DNA virus that can infect cats and cause feline panleukopenia, which is a highly contagious and fatal disease in felines. The sequence of FPV is highly variable, and mutations in the amino acids of its capsid protein play crucial roles in altering viral virulence, immunogenicity, host selection, and other abilities. In this study, the epidemiology of FPV was studied using 746 gastrointestinal swab samples derived from cats that presented gastrointestinal symptoms specifically, diarrhea or vomiting during the period spanning from 2018 to 2022. The overall prevalence of FPV-positive patients among these samples was determined to be 45.4%. Capsid (virion) protein 2 (VP2) gene of each FPV-positive sample was sequenced and amplified, yielding 65 VP2 sequences. Among them, six VP2 gene sequences were detected in the majority of the samples test positive for FPV, and these positive samples originated from a diverse range of geographical locations. These isolates were named FPV-6, FPV-10, FPV-15, FPV-251, FPV-271 and FPV-S2. Additionally, the substitution of Ala300Pro (A300P) in VP2 was detected for the first time in feline-derived FPV (FPV-251). FPV-251 isolate, with this substitution in VP2 protein, exhibited stable proliferative capacity in Madin-Darby canine kidney (MDCK) cells and A72 cells. FPV-271 was selected as the FPV control isolate due to its single amino acid difference from VP2 protein of FPV-251 at position 300 (FPV-271 has alanine, while FPV-251 has proline). After oral infection, both FPV-251 and FPV-271 isolates caused feline panleukopenia, which is characterized by clinical signs of enterocolitis. However, FPV-251 can infect dogs through the oral route and cause gastrointestinal (GI) symptoms with lesions in the intestine and mesenteric lymph nodes (MLNs) of infected dogs. This is the first report on the presence of an A300P substitution in VP2 protein of feline-derived FPV. Additionally, FPV isolate with a substitution of A300P at VP2 protein demonstrated efficient replication capabilities in canine cell lines and the ability to infect dogs.